Thalamocortical Functional Connectivity in Patients With White Matter Hyperintensities - Chen, Chen; Wang, Xiaojing; Cao, Shanshan; Zhang, Jun; Wang, Zhiqi; Pan, Wen; Yang, Jinying; Tian, Yanghua; Qiu, Bensheng; Wei, Qiang; Wang, Kai (Frontiers in Aging Neuroscience, 2021)
Background: White matter hyperintensities (WMH)s is a very common neuroradiological manifestation in the elderly and is an increased risk of dementia and cognitive decline. As we all know, the thalamocortical circuit plays an important part in cognition regulation. However, the role of this circuit in WMHs and its related cognitive deficits is still unclear. Method: Eighty WMH patients and 37 healthy controls (HCs) were enrolled in the current study. WMH patients were divided into a mild WMH group (n = 33) and moderate-severe WMH group (n = 47) according to Fazekas scores. Resting-state functional magnetic resonance imaging (rs-fMRI) data of all participants were collected for thalamocortical functional connectivity (FC) analysis. The analysis was performed in two steps. First, the whole cerebral cortex was divided into six regions of interest (ROIs), which were used as seeds to investigate the changes of FC with the thalamus. Then, the subregion of the thalamus generated in the previous step was used as the seed for FC analysis with the whole brain. Results: In the first step of FC analysis, it was found that precentral gyrus (PrCG)-interthalamic adhesion (ITA) FC values in moderate-severe WMH group were higher than those in HC and mild WMH groups. However, when compared with the HC group, the increase of PrCG-ITA FC values in mild WMH group was not statistically significant. In the second step of FC analysis, the ITA was set as the seed, and compared with the HC group, the results showed that the FC values of the ITA-medial frontal gyrus (MFG) in mild group and moderate-severe WMH groups were significantly increased. In addition, the FC values in moderate-severe group were significantly higher than those in mild group. Finally, it was also found that FC values (PrCG-ITA and ITA-MFG) were significantly correlated with neuropsychological test results for multiple cognitive functions such as memory, execution and attention in WMH patients. Conclusion: Abnormal thalamocortical FC was closely related with cognitive impairments in WMH patients.